The Effectiveness of Educational Interventions In Improving Nurses Knowledge of Dementia Care: A Systematic Review - Ike Ayunda Nasifah; Dianis Wulan Sari; Sylvia Dwi Wahyuni (Jurnal Ners, 2025)
Background: As the global population ages, dementia has emerged as a pressing public health issue. Nurses play a pivotal role in dementia care; however, many lack adequate knowledge and confidence. Targeted educational interventions are essential to improve nursing competencies in dementia care. Objective: This systematic review aimed to evaluate the effectiveness of educational interventions in improving nurses’ knowledge, attitudes, and self-efficacy in dementia care. Methods: A systematic search was conducted across four databases Scopus, PubMed, ProQuest, and Science Direct following PRISMA guidelines. Studies published between 2020 and 2025 were screened using PICOS criteria and assessed for quality using the Joanna Briggs Institute (JBI) appraisal tools. Data were synthesized narratively. Results: Ten studies were included, consisting of quasi-experimental, RCT, and qualitative designs. Interventions such as digital games, virtual reality, simulation, mobile learning, and arts-based methods demonstrated improvements in nurses’ knowledge, empathy, and confidence. Three major themes emerged: (1) enhanced knowledge of dementia, (2) improved attitudes and self-efficacy, and (3) deeper emotional engagement and humanistic understanding. Conclusion: Educational interventions particularly interactive and emotionally engaging formats effectively improve dementia-related competencies in nurses. These findings support the integration of innovative, person-centered training methods into nursing education and practice to enhance dementia care.